Empowering Communities: Legal Enlightenment through Traffic Education in Sofifi - Hakim; Rachman, Saiful (BARAKTI: Journal of Community Service, 2024)
This community service initiative is centered on enhancing legal awareness and promoting compliance with traffic regulations in Sofifi Village, Tidore Kepulauan, in accordance with the Republic of Indonesia Law Number 22 of 2009 concerning Traffic and Road Transportation. Recognizing the pivotal role of motor vehicles in daily activities and their impact on economic and governmental affairs, the initiative employs legal education through community service to elevate public understanding. The involvement of faculty members, students, and local community members underscores the significance of Law No. 2 of 2009 in instilling discipline and traffic safety. The community service activities delve into factors contributing to traffic accidents, driver responsibilities, and legal consequences of violations. Participants gain a better understanding of traffic regulations and cultural norms associated with traffic order. The outcomes are positive, indicating an improvement in knowledge among participants and a heightened sense of responsibility toward traffic safety. The initiative successfully encourages community involvement in maintaining a safer and more organized traffic environment. By focusing on prevention and education, this initiative contributes to the reduction of traffic violations.